We know that
• M is the midpoint of FR.
,
• F(-2,3) and M(3,0).
The midpoint formula is
![M=((x_1+x_2)/(2),(y_1+y_2)/(2))](https://img.qammunity.org/2023/formulas/mathematics/high-school/azlty9lox0olsrspemwjd5v1udpdz43v6k.png)
Where (x_1, y_1) represents point F and (x_2, y_2) represents point R (the missing point). So, our job is to find (x_2, y_2). Let's replace the information we have so far
![(3,0)=((-2+x_2)/(2),(3+y_2)/(2))](https://img.qammunity.org/2023/formulas/mathematics/college/zuzktjve3ts8p8ihs3j2cql0d6ryvw98nh.png)
Let's separate the coordinates, that is, the horizontal coordinate 3 belongs to the horizontal coordinate on the other side of the equation, and the vertical coordinate 0 belongs to the vertical coordinate on the other side of the equation. So, we can rewrite the equation we have as two equations.
![\begin{gathered} 3=(-2+x_2)/(2) \\ 0=(3+y_2)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j06se9qjcm2e2sf57ciwm6gkvhhezhk4v9.png)
The first equation will give us the horizontal coordinate of point R, and the second equation will give us the vertical coordinate of point R. Let's solve both of them
![\begin{gathered} 3=(-2+x_2)/(2)\to6=-2+x_2\to x_2=6+2\to x_2=8 \\ 0=(3+y_2)/(2)\to0=3+y_2\to y_2=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nfbgg0891pq0cfu44uxil8ema69bz4yrok.png)
Therefore, the missing endpoint is (8,-3).
The image below shows all three points.